2010
DOI: 10.1016/j.scitotenv.2010.01.053
|View full text |Cite
|
Sign up to set email alerts
|

Chemical drinking water quality in Ghana: Water costs and scope for advanced treatment

Abstract: 24To reduce child mortality and improve health in Ghana boreholes and wells are being installed across 25 the country by the private sector, NGOs and the Ghanaian government. Water quality is not generally 26 monitored once a water source has been improved. Water supplies were sampled across Ghana from 27 mostly boreholes, wells and rivers as well as some piped water from the different regions and analysed 28for the chemical quality. Chemical water quality was found to exceed the WHO guidelines in 38% of 29 sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
89
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 43 publications
2
89
0
1
Order By: Relevance
“…Mercury was marginally detected in some surface and ground waters in Ghana [4]. Another study conducted in Ghana [5] also found concentrations of lead, uranium and boron above the World Health Organisation (WHO) Guide Values (GVs) in restricted areas. Low metallic content was observed for most water samples analysed in Bangladesh [6].…”
Section: Introductionmentioning
confidence: 95%
“…Mercury was marginally detected in some surface and ground waters in Ghana [4]. Another study conducted in Ghana [5] also found concentrations of lead, uranium and boron above the World Health Organisation (WHO) Guide Values (GVs) in restricted areas. Low metallic content was observed for most water samples analysed in Bangladesh [6].…”
Section: Introductionmentioning
confidence: 95%
“…Emerging anthropogenic pollutants constitute a problem within shallow wells sited in areas of low-cost housing due to inadequate sanitation, household waste disposal, and poor well protection and construction (Sorensen et al 2015). The quality is generally not monitored once a borehole or well is constructed (Rossiter et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…This growth is already taking its toll on the capital in terms of water scarcity, intermittent and irregular supply and limits to expansion of services. But-despite slow progress initially-the country's government succeeded in completing a major policy intervention that became decisive for achieving the Millennium Development Goal on access to water by 2015, namely four projects that added some 300,000 m 3 of water per day to the Greater Accra Metropolitan Area (Republic of Ghana and UNDP 2015). Two of those were the Kpong Water Supply Expansion and the Kpong Intake Expansion Projects, carried out to improve efficiency and increase supply (Andoh 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Nyanti et al (2012) also observed the low dissolved oxygen (DO) in Bakun Dam and anoxic level at 1 to 4 m depths due to decomposition of submerged carbonaceaous materials. Changes in water quality could affect the aquatic life by altering the habitats which ultimately decreases the primary productivity (Rossiter et al 2010). Therefore, it is important to identify the changes in water quality upon impoundment how it would affect the aquatic life.…”
Section: Introductionmentioning
confidence: 99%